Clinical Scenario of Venerophobia in Patients Presenting in Outpatient Department - KC, Shekhar; Adhikary, Manoj; Karn, Dharmendra (Journal of Nepal Health Research Council, 2020)
Background: Venereophobia is fear of getting sexually transmitted disease after first or repeated unprotected sexual activities with unsafe or safe partners. This study aims to study the epidemiological profile, varying clinical presentations and spectrum of psychiatric diagnoses among venereophobia patientsMethods: A cross-sectional, prospective and observational study was conducted among 72 consecutive patients of venereophobia. Patients with symptoms of fear of sexually transmitted infections were evaluated with relevant history and genital examination. Additionally psychiatric evaluation was done for associated diagnoses. Patients with symptoms and clinical signs of sexually transmitted infections were excluded from the study.Results: A total of 68 male and 4 females presented with the symptoms. The mean age of presentation was 25.85±5.15 years. Most of them were either servicemen (38.8%) followed by students (23.6%). After a mean time of 11±10.44 days of sexual activity, patients developed symptoms. Common presentations were genital papules (25%), slough (22.2%) and genital itchy sensation (15.3%). A total of 23(33.8%) patients visited to commercial sex workers with mean spells of visiting 3.2±2.67 times. Factors as regular use of condom and knowledge of overall STI was lacking; while self investigation and multiple doctor visit was common. Pearly penile papule 18(25%) was the commonest diagnosis made on clinical examination. A total of 43 (59.7%) cases were diagnosed with psychiatric conditions, most common being anxiety neurosis (58.1%).Conclusions: Venereophobia was commonly found to be associated with psychiatric illnesses. A proper anamnesis, genital and psychiatric evaluation of this common entity may prevent misdiagnosis and associated complications.Keywords: Phobia; sexually transmitted infections; venereal